Nosná železobetonová konstrukce - Čapek, Andrej (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Bakalářská práce se zaměřuje na návrh nosné monolitické železobetonové konstrukce bytového domu dle zadaných podkladů. Obsahem práce je návrh lokálně podepřené stropní desky nad 2.PP, pro kterou byly vypočteny a porovnávány 3 varianty. Dále se práce věnuje posouzení prefabrikovaného schodiště. K textové části je dále zpracován statický výpočet a výkresy tvarů a výztuže vybraných konstrukcí.

The bachelor's thesis is focused on the design of the load-bearing monolithic reinforced concrete structure of an apartment building according to the specified documents. The content of the work is the design of a locally supported ceiling slab above the 2 underground floor, for which 3 variants were calculated and compared. Furthermore, the work is devoted to the assessment of a prefabricated staircase. In addition to the text part, a static calculation and drawings of shapes and reinforcements of selected structures are processed.
The load-bearing reinforced concrete structure
Keywords: stropní deska; železobeton; monolitická konstrukce; lokálně podepřená deska; trámový strop; vylehčená deska; průvlak; schodiště; scia Engineer; ceiling slab; reinforced concrete; monolithic construction; locally supported slab; beam ceiling; voided slab; girder; staircase; scia Engineer